Effect of social structure and introduction history on genetic diversity and differentiation. Issue 11 (5th May 2021) - Flucher, Sylvia M.; Krapf, Patrick; Arthofer, Wolfgang; Suarez, Andrew V.; Crozier, Ross H.; Steiner, Florian M.; Schlick‐Steiner, Birgit C.
Abstract: Invasive species are a global threat to biodiversity, and understanding their history and biology is a major goal of invasion biology. Population‐genetic approaches allow insights into these features, as population structure is shaped by factors such as invasion history (number, origin and age of introductions) and life‐history traits (e.g., mating system, dispersal capability). We compared the relative importance of these factors by investigating two closely related ants, Tetramorium immigrans and Tetramorium tsushimae, that differ in their social structure and invasion history in North America. We used mitochondrial DNA sequences and microsatellite alleles to estimate the source and number of introduction events of the two species, and compared genetic structure among native and introduced populations. Genetic diversity of both species was strongly reduced in introduced populations, which also differed genetically from native populations. Genetic differentiation between ranges and the reduction in microsatellite diversity were more severe in the more recently introduced and supercolonial T .  tsushimae . However, the loss of mitochondrial haplotype diversity was more pronounced in T .  immigrans, which has single‐queen colonies and was introduced earlier. Tetramorium immigrans was introduced at least twice from Western Europe to North America and once independently to South America. Its monogyny might have limited genetic diversity per introduction, but new mutations and successive introductions over a long time may have added to the gene pool in the introduced range. Polygyny in T .  tsushimae probably facilitated the simultaneous introduction of several queens from a Japanese population to St. Louis, USA. In addition to identifying introduction pathways, our results reveal how social structure can influence the population‐genetic consequences of founder events.